2003
DOI: 10.1002/14651858.cd003798.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Specialist outreach clinics in primary care and rural hospital settings.

Abstract: This review supports the hypothesis that specialist outreach can improve access, outcomes and service use, especially when delivered as part of a multifaceted intervention. The benefits of simple outreach models in urban non-disadvantaged settings seem small. There is a need for good comparative studies of outreach in rural and disadvantaged settings where outreach may confer most benefit to access and health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
254
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(262 citation statements)
references
References 86 publications
2
254
1
5
Order By: Relevance
“…[39][40][41][42][43][44] Behavioral interventions, nutritional counseling, and specialist referrals for pediatric obesity treatment have demonstrated variable short-term as well as long-term success with respect to weight loss or maintenance, depending on the content and intensity of intervention components. [45][46][47][48][49] Patients included in our study did demonstrate significant short-term improvements in diet, activity and weight status while patients were in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42][43][44] Behavioral interventions, nutritional counseling, and specialist referrals for pediatric obesity treatment have demonstrated variable short-term as well as long-term success with respect to weight loss or maintenance, depending on the content and intensity of intervention components. [45][46][47][48][49] Patients included in our study did demonstrate significant short-term improvements in diet, activity and weight status while patients were in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…34 However, few studies have compared the cost of outreach with that of referral care, especially for rural communities, and we identifi ed no studies from low-income and middle-income countries.…”
Section: Increased Use Of Outreach Servicesmentioning
confidence: 99%
“…For example, reviews that considered strategies' eff ects on equity and found promising pro-poor eff ects included those assessing expanded roles for community health workers, 10,11,16 task shifting, 31,32 the expanded use of private service providers, 23,34 strategies to reduce fi nancial barriers to access, 37 and strategies to increase humanresource availability and geographical access. 38,39,43 The other paper in this Series 6 builds on our recommendations and uses data from 15 low-income and middleincome countries to describe how a UNICEF modelling team developed and applied a model that simulates the potential eff ect of implementation of the most promising of these strategies in the context of an equity-based approach to health and nutrition programming.…”
Section: Equity-focused Approachesmentioning
confidence: 99%
“…Gruen et al (2004) conducted a Cochrane review of outreach specialist clinics in primary care and rural settings. They showed that specialist outreach clinics in general practice improved access, but not health outcomes, but more in-depth collaboration with primary care did improve health outcomes, and more efficiently.…”
Section: Introductionmentioning
confidence: 99%